2021
DOI: 10.15586/ijfs.v33i1.1874
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sugar concentration and sugar type on the polyphenol content and antioxidant activity in spiced syrup preparation

Abstract: Besides their culinary roles, spices in the eastern traditional medical practices serve as a medicinal diet therapy. The polyphenol-rich content of these spices contributes to their antioxidant properties, which convey the therapeutic elements. Traditionally, these phytonutrients are orally delivered via herbal decoction, including sugar-syrup-based decoctions. However, the impact of the addition of sugar into polyphenol content and their antioxidant activities are still insufficiently researched. Therefore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…The ability to scavenge DPPH free radical was lowered by as much as over 50%. A similar tendency to decrease antioxidant properties and total phenolic content of honey adulterated with sugar syrups was previously observed, including the dependence of the decrease on the share of sugar syrups [ 12 , 41 , 42 , 43 ]. Such a trend could be explained by the dilution effect: introducing a certain increasing volume of syrup into the honey does not introduce new biologically active compounds, it only dilutes the sample.…”
Section: Resultssupporting
confidence: 79%
“…The ability to scavenge DPPH free radical was lowered by as much as over 50%. A similar tendency to decrease antioxidant properties and total phenolic content of honey adulterated with sugar syrups was previously observed, including the dependence of the decrease on the share of sugar syrups [ 12 , 41 , 42 , 43 ]. Such a trend could be explained by the dilution effect: introducing a certain increasing volume of syrup into the honey does not introduce new biologically active compounds, it only dilutes the sample.…”
Section: Resultssupporting
confidence: 79%
“…A. Kashif-Shaheen, et al [161] used DPPH method for testing the antioxidant activity of hydrolyzed Manno-oligosaccharides, where mannose was the main monosaccharide responsible for this activity. Recent studies indicated clearly that reducing sugars presence infl uences not only the results of antioxidant activity tested by various methods, TPC determined by Folin-Ciocalteu test [162,163].…”
Section: Reported Composition Referencementioning
confidence: 99%